PENGARUH PEMANGKASAN TUNAS APIKAL TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max(L).Merril) - Esrita . (Bioplantae, 2012)
Apical bud prunning is one of the ways to improved growth and yield of soybean. This experiment aime is  to reveal the effect of internode spacing of apical bud prunning that could be the best to increasingsoybean yield and growth. This research was conducted  in Randomized block design, with one factor and five replication, there are, PO:  no apical bud prunning, P1:  apical bud prunning with inter node spacing 10 %, P2:  apical bud prunning with internode spacing20 %, P3:apical bud prunning with internode spacing  30 %. The result showes that soybean apical bud prunning increasing significantly soybean yoeld, and growth parameter, eg. plant height, number of main branches and number of main node.   Key word : internode, apical, bud, prunning.